Rail transport in the Warsaw agglomeration as a determinant of sustainable transport - Alan Beroud; Ewelina Golańska (Przegląd Komunikacyjny)
Abstract: This article describes the conditions for the functioning of railway transport in the area of the Warsaw agglomeration, the legal conditions for the functioning of metropolitan areas and attempts to define the areas of development and limitations for sustainable transport. Due to the professional experience of the authors, an additional issue discussed in this study will be the functioning of rail transport on the example of the Fast Urban Railway sp. z o.o. in Warsaw. Keywords: Agglomeration; Railway transport; Suburban train